SOLIDARITAS ETNIS JAWA PERANTAUAN DI DESA LAKAWALI KABUPATEN LUWU TIMUR - Nurlela Nurlela; Firdaus W Suhaeb; Muhammad Syukur (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2023)
This deep understanding of the dynamics of Overseas Javanese solidarity is not only important to explain social interactions at the local level but also has important implications for the development of contemporary science, especially in the field of Anthropology / Sociology in the context of overseas Javanese solidarity.  This type of research is qualitative descriptive research using the theoretical approach of solidarity Bronislaw Malinowski. Data collection techniques in this study are observation, interviews and documentation. The results of this study show that the form of solidarity built in overseas Javanese in Lakawali Village is integrative solidarity and regulative solidarity. Integrative solidarity of Overseas Javanese in Lakawali Village is manifested in various attitudes of interdependence and cooperation which became the forerunner of the formation of solidarity in daily life, while regulative solidarity in Overseas Javanese in Lakawali Village, East Luwu Regency is characterized by the existence of cultural values and social norms such as politeness values and moral values that form solidarity with the community.